ONION PEEL APPEARANCE IN BALOS CONCENTRIC SCLEROSIS-A VARIANT OF MULTIPLE SCLEROSIS - Arif, Saeed; Wali, Muhammad Waseem; Slehria, Atiq ur Rehman; Khalid, Hina; Malik, Hamza (Journal of Ayub Medical College Abbottabad, 2015)
Balo's concentric sclerosis (BCS) is a variant of multiple sclerosis (MS). It may present as a lesion clinically and radiologically indistinguishable from brain tumour particularly on computerized tomography (CT) scans. Diagnosis only gets clear when magnetic resonance imaging and spectroscopy (MRI & MRS) and brain biopsy is done. We report a case of 30 year old male with progressive headache and left hemi paresis for 3 weeks. There was upper motor neuron (UMN) facial palsy on the left with bilateral papilledema. CT scan of brain showed large hypo-dense area in right frontoparietal lobe consistent with brain tumour. On MRI the diagnosis of BCS was made on basis of concentric lesions of myelinated and demyelinated rings. Demyelination was confirmed on brain biopsy. Keywords: Balo's concentric sclerosis, Multiple sclerosis, Tumefactive demyelinating lesion